Development of differential inductive transducer system for accurate position measurement - Abdulwahab, Deji (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
This research work focuses on the design, simulation and implementation of differential inductive sensor. The importance of the findings of this work lies in the issues related to non-linearity, insensitivity, and errors for better accuracy. Also, this work is highlighting some of the areas of research concern such as Sensing Range, core operating from both sides as seesaw. Issues of environmental conditions such as (air density, temperature, wind) are explored. The core speed/acceleration, displacement when used as a seesaw, and its fluctuations, calibration are also characterized. The idea is using inductive coils as transducer elements responding to changes in the parameter being sensed. This phenomenon is the result of simple movement of a core position bringing about proportionate changes in the inductance of the circuit, and hence ultimately in the output frequency parameters. The output parameters include frequency, duty cycle, current, voltage, frequency, frequency hysteresis, speed, acceleration, kinematics, pressure, range of oscillation, angulation, Impedance voltage, Magnetic field strength, and Transfer function. The concept developed in this thesis is implemented into having a vibration and oscillation device capable of harvesting energy sources. The scope of this work lies in the design of electromechanical and servomechanism vibration and oscillation, harvesting devices. The device is an improved pressure sensor design, wind energy sensor in applications such as in liquid level characterization. The visualization of inductive sensing for data acquisition increases the understanding of the behavior of metal detection. Coupled with signal processing methods the size and position of metallic pieces and food industry can be realized. The details of the inductive-changes differential sensory system, its excitation from a source and performance against different core material under similar working conditions are presented in this thesis. The utility of this work lies broadly in data acquisition system making use of differential sensors. It has provided for a detailed design and development of a system that can be implemented for position sensing acquiring data from oscillation deflections in millimeter and micrometer range values. The method used is an alternative to the current data acquisition systems using cantilever mechanism by Bruno 2013 and 2014. The circuit is analyzed before it is simulated using ORCAD PSPICE and MATLAB code. A comparison between the simulation and experimental results show the circuit's preferential utility over the circuits currently in use for similar applications. A FSC margin of 0.01% resolution is found and reported. Through experiments, frequency and inductance responses are obtained to show that the proposed system is reliable with the preferential advantages of being accurate. Hence, the frequency output as a result of differential comparison from counter 1 and counter 2 of the design is an optimized output since this kind of novelty does not exist in literature as seen ultimately in the currently obtained output in Bruno 2013, 2014, Ezzat 2011, 2012 etc.